Analysis of Factors Related to Bone Density in Trimester III Pregnant Women in The Working Area of Community Health Center of Andalas Padang - Violita Dianatha Puteri; Athica Oviana; Roza Sriyanti; Cimi Ilmiawati (Science Midwifery, 2021)
The decrease of bone density becomes a serious health problem because of its increasing prevalence worldwide, especially for women. Parity is one of the factors that can affect bone density, apart from physical activity, consumption of caffeinated and carbonated drinks, intake of protein, magnesium, phosphorus, calcium, and serum 25(OH)D levels. This study aimed to comprehensively analyze the factors associated with bone density in pregnant women. This cross-sectional study was conducted in the working area of Community Health Center of Andalas Padang towards 73 pregnant women in the third trimester with a purposive sampling technique.Structured interviews were conducted by using a semi-quantitative food frequency questionnaire (nutritional intake), Baecke's questionnaire (physical activity) and examination of serum 25(OH)D levels using the ELISA method. Data were analyzed by using One Way ANOVA, Kruskal-Wallis test and multiple linear regression. The results of statistical tests showed that there was no significant relation (p> 0.05) among parity, physical activity, serum 25 (OH) D levels, consumption of caffeinated and carbonated drinks, intake of protein, phosphorus, magnesium, and calcium on bone density at pregnant women. The dominant factor related to bone density are parity (adjustedR2=0,191 ; standardized β coefficient= -0,357 ; p=0,004) and calcium intake (adjusted R2=0,191;standardized β coefficient=0,308 ; p=0,005). The conclusion of this study is that calcium intake and parity play important roles in bone density in pregnant women.